Pyrolysis Characteristics of Empty Fruit Bunches at Different Temperatures and Heating Rates - Hyeongtak Ko; Myeongjong Lee; Rumduol Sen; Jeongwoo Choi; Seacheon Oh (Energies)
EFB is a biomass waste primarily generated in Southeast Asia, and its pyrolysis enables both waste management and conversion into valuable products. In pyrolysis, the heating rate is a crucial factor; however, studies on its influence on EFB are extremely limited. This study investigates the pyrolysis characteristics of EFB by analyzing product properties based on reaction temperature and heating rate. TGA showed that the thermal decomposition of EFB begins at approximately 210 °C and is largely complete by 400 °C. Furthermore, kinetic analysis using TGA data, applying both differential and integral methods, revealed distinct trends. Through pyrolysis experiments using a fixed-bed reactor, the yield analysis of products under varying reaction temperatures and heating rates demonstrated that higher temperatures promote pyrolysis, leading to a decrease in biochar yield and an increase in gas product yield. For liquid products, a higher heating rate suppressed secondary reactions and led to an increase in the yield of the aqueous phase. Gas product characterization revealed that CO and CO2 formation began simultaneously at approximately 270 °C. GC-MS analysis of the liquid products recovered under different pyrolysis conditions showed that most compounds contained oxygen, originating from hemicellulose, cellulose, and lignin. Additionally, FT-IR analysis of the biochar confirmed that oxygen-containing functional groups decomposed as pyrolysis progressed, and the presence of turbostratic carbon and crystallinity influenced by trace inorganic elements was identified.